(3QSGdI JbdjO GdeJbi JbdjO CUes - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3EYde hfabc Gdehdi hefMc SHjd GdgOi ef bGFe GdReGf gGOi GdeSJLjHjf GdefJbe ef GdeTQcjf hGdeGQbjf s
(3BNQgG (B:s
(3Ydi JhGJQ fYeI hGcJH GdejKGb Ydi GdeSJLjHjf HVHW GdMdjI hCMcGe GdTgGOI hcf Hge QajbkG hfYe GdfUjQ GdeYjf SHMGfg hMOg dGTQjc dg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B23s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdJhMjO hGdedd hGdfMds